Heritage buildings as a contribution to the contemporary city: the relocation of Braga’s District Archive - Silva, João Pedro Costa Pereira (2020)
This paper reflects on the ability to adapt buildings with relevant heritage and historical value to different uses and functions. A case study is presented: The relocation of Braga?s District Archive from the former Archbishop?s Palace in Largo do Paço, a building dating back to the XIVth century confined within the Historical Center?s buffer zone, into a modernist building located in Abade Loureira street, North of the original complex and outside the medieval walled city. The methodological approach and the processes associated with the intervention are presented according to the analysis of the proposed program, rather than by the formal and symbolic features of the building itself. Extensive in-situ surveys took place at the two buildings, comparing both the present and the proposed solution. Based on this analysis, the Program?s adequacy is discussed, displaying the advantages and disadvantages of this change and how it may affect the mission of the District Archive.